The Narrator's Search for her Identity in Margaret Atwood's Surfacing - Maudher Dakheel, Rana; Lateef Jabbar, Amjed (Al-Adab Journal, 2018)
Margaret Eleanor Atwood is born on November 18, 1939, Ottawa, Ontario, Canada. She received her undergraduate degree from Victoria College at the University of Toronto and her master's degree from Radcliffe College. Atwood is a Canadian writer best known for her novels, which include: The Edible Woman (1969), Surfacing (1972), Lady Oracle (1976), Life Before Man (1979), Bodily Harm (1981), The Handmaid's Tale (1985), Cat's Eye (1988), The Robber Bride (1993), Alias Grace (1996) and The Blind Assassin (1998). Atwood is a famous writer, and her novels are best sold all over the world. She has been labelled as a Canadian nationalist, feminist, and even a gothic writer. She is well known internationally in the USA, Europe, and Australia. This research aims at showing throughout Surfacing, the way Atwood portraits the narrator as a woman searching for her own identity.